Challenges in measuring nitrogen isotope signatures in inorganic nitrogen forms: An interlaboratory comparison of three common measurement approaches. (13th September 2022) - Biasi, Christina; Jokinen, Simo; Prommer, Judith; Ambus, Per; Dörsch, Peter; Yu, Longfei; Granger, Steve; Boeckx, Pascal; Van Nieuland, Katja; Brüggemann, Nicolas; Wissel, Holger; Voropaev, Andrey; et al.
Abstract : Rationale: Stable isotope approaches are increasingly applied to better understand the cycling of inorganic nitrogen (Ni ) forms, key limiting nutrients in terrestrial and aquatic ecosystems. A systematic comparison of the accuracy and precision of the most commonly used methods to analyze δ 15 N in NO3 − and NH4 + and interlaboratory comparison tests to evaluate the comparability of isotope results between laboratories are, however, still lacking. Methods: Here, we conducted an interlaboratory comparison involving 10 European laboratories to compare different methods and laboratory performance to measure δ 15 N in NO3 − and NH4 + . The approaches tested were (a) microdiffusion (MD), (b) chemical conversion (CM), which transforms Ni to either N2 O (CM‐N2 O) or N2 (CM‐N2 ), and (c) the denitrifier (DN) methods. Results: The study showed that standards in their single forms were reasonably replicated by the different methods and laboratories, with laboratories applying CM‐N2 O performing superior for both NO3 − and NH4 +, followed by DN. Laboratories using MD significantly underestimated the "true" values due to incomplete recovery and also those using CM‐N2 showed issues with isotope fractionation. Most methods and laboratories underestimated the at% 15 N of Ni of labeled standards in their single forms, but relative errors were within maximal 6% deviation from the real value and therefore acceptable. The results showed further that MD is strongly biased by nonspecificity. The results of the environmental samples were generally highly variable, with standard deviations (SD) of up to ± 8.4‰ for NO3 − and ± 32.9‰ for NH4 + ; SDs within laboratories were found to be considerably lower (on average 3.1‰). The variability could not be connected to any single factor but next to errors due to blank contamination, isotope normalization, and fractionation, and also matrix effects and analytical errors have to be considered. Conclusions: The inconsistency among all methods and laboratories raises concern about reported δ 15 N values particularly from environmental samples.